Engineered Lysins With Customized Lytic Activities Against Enterococci and Staphylococci - Binte Muhammad Jai, Hana Sakina; Dam, Linh Chi; Tay, Lowella Servito; Koh, Jodi Jia Wei; Loo, Hooi Linn; Kline, Kimberly A.; Goh, Boon Chong (Frontiers in Microbiology, 2020)
The emergence of multidrug-resistant bacteria has made minor bacterial infections incurable with many existing antibiotics. Lysins are phage-encoded peptidoglycan hydrolases that have demonstrated therapeutic potential as a novel class of antimicrobials. The modular architecture of lysins enables the functional domains - catalytic domain (CD) and cell wall binding domain (CBD) - to be shuffled to create novel lysins. The CD is classically thought to be only involved in peptidoglycan hydrolysis whereas the CBD dictates the lytic spectrum of a lysin. While there are many studies that extended the lytic spectrum of a lysin by domain swapping, few have managed to introduce species specificity in a chimeric lysin. In this work, we constructed two chimeric lysins by swapping the CBDs of two parent lysins with different lytic spectra against enterococci and staphylococci. We showed that these chimeric lysins exhibited customized lytic spectra distinct from the parent lysins. Notably, the chimeric lysin P10N-V12C, which comprises a narrow-spectrum CD fused with a broad-spectrum CBD, displayed species specificity not lysing Enterococcus faecium while targeting Enterococcus faecalis and staphylococci. Such species specificity can be attributed to the narrow-spectrum CD of the chimeric lysin. Using flow cytometry and confocal microscopy, we found that the E. faecium cells that were treated with P10N-V12C are less viable with compromised membranes yet remained morphologically-intact. Our results suggest that while the CBD is a major determinant of the lytic spectrum of a lysin, the CD is also responsible in the composition of the final lytic spectrum, especially when it pertains to species-specificity.